The relationship between women’s childbirth experiences and their maternal attachment and the risk of postpartum depression - Muslu, Ayşegül; Erciyas, Şeyma Kilci; Cindaş, Pakize; Atan, Şenay Ünsal (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. This descriptive study was conducted to examine the effects of the childbirth experiences of mothers on their maternal attachment and postnatal depression. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study was conducted with 315 mothers who agreed to participate in the study in Obstetrics and Gynecology Hospital between 2 September 2019 and 25 February 2020. A “Personal Information Form”, “Childbirth Expectation and Experience Questionnaire (CEEQ)”, “Maternal Attachment Inventory (MAI)”, and “Edinburgh Postnatal Depression Scale (EPDS)” were used to collect data. The data were analyzed with the IBM SPSS v23 program. Independent-samples t test, one-way analysis of variance (ANOVA), and Pearson’s correlation test were used in the analyses. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The mean postpartum depression mean score of the participants was 4.3±5.9, and 23% of them were at risk of depression. The mean maternal attachment score of participants was determined as 85.2±4.6, and their mean birth experience score was 3.0±3.1. A positive and significant relationship was found between more than half of the items of Childbirth Expectation and Experience Questionnaire and general satisfaction (p≤0.05). The childbirth experience scores of the participants were not significantly related to their maternal attachment and postpartum depression scores (p>0.05). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. In this study, no significant relationship was found between the childbirth experiences of women and their maternal attachment or postpartum depression levels.